Demand for grazing on public lands: a disequilibrium approach. - Bhattacharya, Arunava; Narayanan, Rangsean; MacDiarmid, Thomas R. (Land Economics, 1996)
A study was conducted to estimate a demand function for grazing on western public rangelands. As the federal government sets the grazing fee and rations the quantity of Animal Unit Months (AUMs), a disequilibrium model was developed. The proposed model was estimated using panel data from ten western states covering the period from 1966 to 1991. The estimate of own-price elasticity of demand (-0.178) indicates a 0.82 percent revenue gain for a 1 percent fee increase. Results demonstrate that most western states experienced excess supply of AUMs since the mid-1980s, indicating a relatively high fee. The levels of demand and effective supply vary considerably across states; this suggests that state- or region-specific factors should be incorporated in setting the grazing fee.